2011
DOI: 10.1088/0004-637x/730/1/8
|View full text |Cite
|
Sign up to set email alerts
|

ON THE REDSHIFT EVOLUTION OF THE Lyα ESCAPE FRACTION AND THE DUST CONTENT OF GALAXIES

Abstract: The Lyα emission line has been proven a powerful tool by which to study evolving galaxies at the highest redshifts. However, in order to use Lyα as a physical probe of galaxies, it becomes vital to know the Lyα escape fraction (f Lyα esc ). Unfortunately, due to the resonant nature of Lyα, f Lyα esc may vary unpredictably and requires empirical measurement. Here we compile Lyα luminosity functions between redshift z=0 and 8 and, combined with Hα and ultraviolet data, assess how f Lyα esc evolves with redshift.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

75
343
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(430 citation statements)
references
References 109 publications
75
343
11
1
Order By: Relevance
“…The detected fraction for Lyα emission at z = 2 to 3, inferred from comparing the Lyα luminosity density and Hα or H β luminosity density, is about 5% (e.g. Hayes et al 2011;Ciardullo et al 2014). This fraction is consistent with the ratio between the star formation rate density inferred from Lyα emitters and that from quasar-Lyα cross-correlation in this work (see the blue and red points in Figure 13).…”
Section: Escape Fraction and Detected Fractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detected fraction for Lyα emission at z = 2 to 3, inferred from comparing the Lyα luminosity density and Hα or H β luminosity density, is about 5% (e.g. Hayes et al 2011;Ciardullo et al 2014). This fraction is consistent with the ratio between the star formation rate density inferred from Lyα emitters and that from quasar-Lyα cross-correlation in this work (see the blue and red points in Figure 13).…”
Section: Escape Fraction and Detected Fractionmentioning
confidence: 99%
“…Integrating the luminosity functions of Lyα emitting galaxies, assuming a power-law extrapolation for the faint end slope, has revealed that the comoving volume emissivity of Lyα photons declines significantly from z ∼ 6 to z ∼ 2 (Cassata et al 2011, Gronwall et al 2007, Ouchi et al 2008). This behaviour can be compared to the opposite evolution in redshift of galaxies measured in optically thin parts of the rest-frame UV spectrum (or using the Hα line, e.g., Hayes et al 2011). This comparison has been used to infer (e.g., by Hayes et al 2011 andCassata et al 2011) that the escape fraction of Lyα photons produced in star forming regions has significantly decreased from z = 6 to z = 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This adds to the difficulty of determining the escape fraction of Lyα photons originated directly by stellar ionization along the history of the Universe (Hayes et al 2011). A further correction should be applied to the procedure used to convert Lyα luminosity into number of ionizing photons, and thus star formation rate.…”
Section: Dust Reflectionmentioning
confidence: 99%
“…Gas cooling may boost the fluxes of Lyα and HeIIλ1640 (Yang et al 2006;Dijkstra 2009), and Lyα may be absorbed by the partly neutral IGM at z 6 (e.g. Hayes et al 2011). Here, we consider an alternative approach to probing the Pop III IMF, through the measurement of direct star light from Pop III star clusters.…”
Section: Introductionmentioning
confidence: 99%